2003
DOI: 10.1002/jmv.10575
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for potentially xenozoonotic viruses in New Zealand pigs

Abstract: Shortage of human donor organs for transplantation has prompted evaluation of animals as an alternative donor source. Pigs are the most acceptable candidate animals but issues of xenozoonozes remain. Despite careful monitoring of high-health-status (HHS) pigs, there is still a risk that their tissues may carry infectious agents. Furthermore, pathogens which are significant in xenotransplantation are not necessarily those of veterinary importance. The detection of these potentially transmissible infectious agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Pig cells were obtained from pigs of Large White and Cambrough breeds that had been screened extensively for conventional microorganisms and for viruses of particular relevance to xenotransplantation, namely PLHV, PCMV, and PCV. In none of the tested donor pigs were these viruses found (12).…”
mentioning
confidence: 99%
“…Pig cells were obtained from pigs of Large White and Cambrough breeds that had been screened extensively for conventional microorganisms and for viruses of particular relevance to xenotransplantation, namely PLHV, PCMV, and PCV. In none of the tested donor pigs were these viruses found (12).…”
mentioning
confidence: 99%
“…[27]]. During this period the company thas published about the microbial safety of the source animals [92,93], and presented some preclinical efficacy data in nonhuman primates [94]. From the clinical trials the safety aspects have been published, documenting microbial safety and the absence of PERV transmission [95]: the first report on efficacy documented a reduction in hypoglycemia unawareness, together with a reduction in glycosylated hemoglobin and presence of circulating porcine C-peptide in some of the patients [96].…”
Section: Approved Xenogeneic Cell Therapy Trialmentioning
confidence: 95%
“…Domestic swine were the most-studied animal species (n = 428 studies) and prevalence 336 surveys conducted in all continents except Africa, reported detection of HEV, even in 'high 337 health' swine herds (Garkavenko et al, 2004). Prevalence of detection of HEV RNA was 338 reported to range from 0 to 86.2% in swine on-farm ( M a n u s c r i p t 16 T 2 = 4.65); and prevalence of shedding in finishers in North America ranged from 0 to 47.1% 343 with MA summary estimate 23.0% (95% CI (13.2%, 35.8%); I 2 = 89.31; T 2 = 1.18) ( Table 3).…”
Section: Iii)mentioning
confidence: 98%